Pharmacists reinventing their roles to effectively respond to COVID-19: a global report from the international pharmacists for anticoagulation care taskforce (iPACT) - Filipa Alves da Costa; Vivian Lee; Silvana Nair Leite; Maria Dolores Murillo; Tom Menge; Sotiris Antoniou (Taylor & Francis Group, 2020)
SARS-CoV2 is dramatically impacting the global population. Worldwide, pharmacists are changing their roles and being increasingly recognized for their role as essential service providers. This commentary provides some examples collected from Asia, Europe, the Americas and Africa, ranging from essential services to meet human rights basic needs, extended generalist services developed to ensure continuity of care and supply of essential medicines to the development of differentiated extended responsibilities in emergency care. All examples were collected using a network of pharmacists from 27 countries, representing various areas of pharmacy practice, education and research and outreaching to include patient advocates. Selected services illustrate good practice, capability to adapt and contribution to universal health coverage. Above all, it demonstrates the commitment and innovation of the pharmaceutical workforce in the fight against COVID-19.